Health and Behavioral Survey of over 8000 Finnish Cats - Vapalahti, Katariina; Virtala, Anna-Maija; Joensuu, Tara A.; Tiira, Katriina; Tähtinen, Jaana; Lohi, Hannes (Frontiers in Veterinary Science, 2016)
A comprehensive feline health survey was conducted to reveal breed-specific inheritable diseases in Finnish pedigree cats for genetic research. Prevalences of 19 disease categories and 227 feline diseases were defined in a study population of 8175 cats belonging to 30 breeds. Dental and oral diseases with a prevalence of 28% and dental calculus and gingivitis (21% and 8%, respectively) were the most prevalent disease category and diseases among all cats and in most of the breeds. An exception was Korats, which were more often affected by the diseases of the respiratory tract (23%) and asthma (19%). Other prevalent disease categories affected various organ systems such as the skin (12%), the urinary system (12%), the digestive tract (11%), eyes, (10%), the musculoskeletal system (10%), and genitals of female cats (17%). Prevalent health or developmental issues included repetitive vomiting (4%), tail kink (4%), feline odontoclastic resorption lesion (FORL) (4%), urinary tract infections (4%), as well as caesarean section (6%) and stillborn kittens (6%) among female cats. We found 57 breed-specific conditions by Fisher’s exact tests and logistic regression analyses, including 32 previously described and 19 new breed-specific diseases. The genetic defect has already been found in six of them: polycystic kidney disease (PKD), progressive retinal atrophy (PRA), hypertrophic cardiomyopathy (HCM) and three types of tail malformations. Behavioral profiling revealed breed-specific traits, such as an increased human avoidance in British Short and Longhairs and a higher level of aggression in Turkish vans. Our epidemiological study reveals the overall health profile in Finnish pure and mixed breed cats and identifies many breed-specific conditions without molecular identity for genetic research.